Development and Selection of the Human Vγ9Vδ2+ T-Cell Repertoire - Willcox, Carrie R.; Davey, Martin S.; Willcox, Benjamin E. (Frontiers in Immunology, 2018)
Vγ9Vδ2+ lymphocytes are among the first T-cells to develop in the human fetus, and are the predominant peripheral blood γδ T-cell population in most adults. Capable of broad polyclonal responses to pyrophosphate antigens (pAg), they are implicated in immunity to a diverse range of infections. Previously Vγ9Vδ2+ development was thought to involve postnatal selection and amplification of public Vγ9 clonotypes in response to microbial stimuli. However, recent data indicate the Vγ9Vδ2+ TCR repertoire, which is generated early in gestation, is dominated by public Vγ9 clonotypes from birth. These chains bear highly distinct features compared to Vγ9 chains from Vδ1+ T-cells, due either to temporal differences in recombination of each subset, and/or potentially prenatal selection of pAg reactive clonotypes. While these processes result in a semi-invariant repertoire featuring Vγ9 sequences pre-configured for pAg recognition, alterations in TCRδ repertoires between neonate and adult suggest either peripheral selection of clonotypes responsive to microbial antigens, or altered postnatal thymic output of Vγ9Vδ2+ T-cells. Interestingly, some individuals demonstrate private Vγ9Vδ2+ expansions with distinct effector phenotypes, suggestive of selective expansion in response to microbial stimulation. The Vγ9Vδ2+ T-cell subset therefore exhibits many features common to mouse γδ T-cell subsets, including early development, a semi-invariant TCR repertoire, and a reliance on butyrophilin (BTN)-like molecules in antigen recognition. However, importantly Vγ9Vδ2+ T-cells retain TCR sensitivity after acquiring an effector phenotype. We outline a model for Vγ9Vδ2+ T-cell development and selection involving innate prenatal repertoire focussing, followed by postnatal repertoire shifts driven by microbial infection and/or altered thymic output.